قياس وتحليل تكاليف التضخم وأثرها على مستويات المعيشة بالعراق للمدّة 1990-2012 (المجلة العراقية للعلوم الاقتصادية, 2018)
Inflation is always a challenge for most of the economies of countries in the world, because of its undesirable effects, that are costs borne by society, and Iraq are among the countries that have suffered from inflationary pressures for several decades. These inflationary pressures pay for members of the Iraqi community in the form of costs, without knowing their amount and size, and for the purpose of knowing their amount and embark on measuring them, we, in this research, estimate the cost of inflation, by using the long-term equilibrium relationship between the real cash balance, as a percentage of real income (prices fixed GDP) and the price of the Iraqi Central Bank's policy over the period 1990-2012. The average total cost is (0.2430) for the annual average inflation, which is (71.4%) for the period 1990-2012. In order to achieve the objectives of the research, the indicators of living standards are estimating in real terms, after testing the stability of the inflation cost of data series, an average per capita gross domestic product, private consumption spending (family), line of absolute poverty before and after deducting the cost of the ration card, and verify the existence of a cointegration relationship between them. One of the main conclusions reached by the research, said that the money in the Iraqi economy, in addition to being a necessary commodity for the purposes of the transaction, it is a political commodity to be virtually the outcome of the export of oil. It is influenced by the political situation experienced by Iraq since the 1990-2012 and up to date, and that the average annual inflation (71.4%) resulted in an average inflation costs by (0.2430), has led to a decline in living standards in the Iraqi economy by (0.164%) and ( 0.171%) for the period from 1990 to 2012.